2013
DOI: 10.7205/milmed-d-12-00177
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Secondary Insults of Traumatic Brain Injury in Patients Transported by Critical Care Air Transport Teams From Iraq/Afghanistan: 2003–2006

Abstract: Traumatic brain injury patients are susceptible to secondary insults to the injured brain. A retrospective cohort study was conducted to describe the occurrence of secondary insults in 63 combat casualties with severe isolated traumatic brain injury who were transported by the U.S. Air Force Critical Care Air Transport Teams (CCATT) from 2003 through 2006. Data were obtained from the Wartime Critical Care Air Transport Database, which describes the patient's physiological state and care as they are transported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Multiple studies have been conducted evaluating the en route care of patients during transport from point of injury to first MTF (role 2 and/or 3) 5,12,[14][15][16][17][18][19][20][21][22] and out of theater to the role 4 medical center in Landstuhl, Germany. 12,[19][20][21][22][23][24][25][26][27][28] A few published reports have described patients treated by individual forward surgical teams (role 2) during specific deployments, but these studies do not include information related to patient transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have been conducted evaluating the en route care of patients during transport from point of injury to first MTF (role 2 and/or 3) 5,12,[14][15][16][17][18][19][20][21][22] and out of theater to the role 4 medical center in Landstuhl, Germany. 12,[19][20][21][22][23][24][25][26][27][28] A few published reports have described patients treated by individual forward surgical teams (role 2) during specific deployments, but these studies do not include information related to patient transport.…”
Section: Discussionmentioning
confidence: 99%
“…12,[19][20][21][22][23][24][25][26][27][28] A few published reports have described patients treated by individual forward surgical teams (role 2) during specific deployments, but these studies do not include information related to patient transport. These reports described cases and procedures performed by the surgical teams from data sets collected prospectively by the surgical team.…”
Section: Discussionmentioning
confidence: 99%
“…The austere ERC environment poses challenges to the monitoring and care of patients with TBI, and the stresses of fl ight can potentially contribute to secondary neurological insults (Fang, Dorlac, Allan, & Dorlac, 2010;Goodman et al, 2010). A study was conducted of secondary insults (e.g., hypotension, hypoxia, hyperthermia, hypothermia, hyperglycemia, and hypertension) which occurred in patients with severe TBI who were evacuated from Iraq or Afghanistan from 2003 to 2006 (Dukes, Bridges, & Johantgen, 2013). This study found that hyperthermia was the secondary insult documented most frequently, with 47% of the patients suffering at least one episode of an increased temperature.…”
Section: Implications For Further Innovation Research and Policymentioning
confidence: 99%
“…For obvious ethical reasons, a prospective randomized controlled clinical study concerning the adverse effects of secondary insults on outcomes from TBI has never been done [1,4]. However, an increasing body of experimental results and clinical retrospective studies in the past few decades have demonstrated that such secondary insults occurred frequently after TBI and exerted a powerful, detrimental influence on recovery from TBI [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 96%
“…Primary injury refers to the immediate, irreversible parenchymal and vessel damage occurring at the time of injury, while secondary injury refers to potentially avoidable damage that occurs at variable times after the initial injury and can be further aggravated and prolonged or even initiated by secondary insults [6][7][8][9][10][11] (Figure 1). Secondary insults are most common immediately after the primary injury, but can also occur throughout the whole recovery period.…”
Section: Introductionmentioning
confidence: 99%